Treating online inappropriate sexualised behaviour. (12th September 2016) - Chandler, Robert J.; Swift, Charlotte; Goodman, Wendy
Abstract : Purpose: The purpose of this paper is to evaluate the use of cognitive behavioural approaches to treat a gentleman with a learning disability who had been reported to the police for allegedly making contact with children using social media in an attempt to initiate a romantic relationship using a single case design. Design/methodology/approach: An 11 session cognitive behavioural intervention was employed, comprising of index offence analysis, challenging distorted cognitions related to the offence, developing an internal focus for responsibility and psychoeducation with regards to "staying safe" online. Findings: Follow up data demonstrated no improvements in victim empathy, nor in agreement ratings in terms of key cognitions associated with responsibility for offending behaviour. Research limitations/implications: Whilst treatment efficacy was not established, this case study raises important questions that go beyond the single case design. Whilst the gentleman reported becoming "safer" in terms of initiating contact with unknown people via social media, this could not be substantiated, and is indicative of the cardinal difficulty of monitoring online recidivism. Generalisability of findings to the wider learning disability population is limited by a single case design. Originality/value: This is the first published case study to the authors knowledge to evaluate cognitive behavioural approaches to reduce antisocial internet related behaviour in a forensic learning disability setting. Findings of considered within the context of the concept of minimisation of offending behaviour, the concept of "counterfeit deviance", and also how best to measure therapeutic change within this population.